The development of a comprehensive records management program for the University of the Philippines Diliman - Dimalanta, Richard Paul C. (School of Library and Information Studies, University of the Philippines, Diliman, 2019)
Republic Act 9470 or the National Archives of the Philippines Act provided the legal framework to which records management in government agencies are regulated. The law specifically requires all government agencies including State Universities like the University of the Philippines (UP) Diliman to establish a records management program, conduct of inventory of public records, and establishment of records disposition schedules, among others. Even though attempts have been made to standardize and formalize the records management program for UP Diliman, the University still doesn't have a records management program for all offices of the University.